Modelling the flow of water in stratified layers of sand (2011)
"The phenomenon of deflection of flow of water in porous media of different porosities with porosity ratio, ᵠ, is similar to fact that there is deviation in fluid flow in a pair of media of different densities. Theoretically, the relationship between preferred direction of flow of water, 0, and the sand layers of porosity ratio,ᵠ was found to be cos 0=nᵠ while experimentally it was obtained to be cos 0=1.98 In ᵠ+1.13 (0.5951≤ᵠ≤0.9634). Thereafter, when the theoretical equation was compared with the experimental result, the value of n ranging from 0 to 1 were found to be appropriate for the theoretical equation to be valid "